The effectiveness of promotional efforts towards Nestle beverages / Nur Hazwani Masor@Mansor - Masor@Mansor, Nur Hazwani (Faculty of Business and Management, 2007)
This research was conducted for the purpose of "The Effectiveness of Promotional Effort towards Nestle Beverages". The main objective of this research was to determine the effectiveness of the existing promotions strategies used by Nestle Food Service, to determine the level of effectiveness of promotion that had done by Nestle, to identify which promotional tools that have been used by Nestle is the most influencing the customer, to determine relationship between the promotional tools towards the effectiveness of promotional effort. According to the Marketing Manager of Nestle Food Service, there are not many promotions that have been used by Nestle Food Services. There were only focusing on certain promotional strategies that they think most valuable for them. Thus this research was conducted in order to identify which promotional tools those are most effective that can be implementing to the customer. For the purpose of the study, descriptive research design had been adopted. The respondents of this study was potential customers that using the Nestle beverages. 70 questionnaires had been distributed to the customers who recently used the Nestle beverages. The researcher had used simple random sampling as the sampling techniques. In this study, descriptive statistic had been used to interpret the data such as reliability testing, frequency tables, and one way ANOVA for the hypothesis testing. From the findings, the most effective promotional strategies that Nestle Food Services that were preferred by the customers was the sales promotion and direct marketing. Thus Nestle should take into consideration that direct marketing is one of the strategies that also preferred by the customers because it can save their time in order to get the products that they want. This research also recommends some aspects that need to be improved in order to make the promotional strategies more effective.